Computer Science - CACIC 2017 : 23rd Argentine Congress, La Plata, Argentina, October 9-13, 2017, Revised selected papers /: 23rd Argentine Congress, La Plata, Argentina, October 9-13, 2017, Revised selected papers. ([2018]) - Unknown
No abstract available